A mystery or a route? a systematic literature review of transcreation and translation studies - Zhu, He; Ang, Lay Hoon; Abdullah, Muhammad Alif Redzuan; Zhu, Hongxiang (Academy Publication, 2024)
Transcreation is an inter-cultural and inter-linguistic activity, which has obtained particular academic interest recently. However, few studies have reviewed the current status quo on transcreation systematically, although transcreation has been applied in various fields such as literature and advertising translation. In this study, a systematic literature review is conducted to shed light on this topic by identifying and analysing genres, foci, methods, and theories related to transcreation. The databases cover Scopus, Web of Science and CNKI from 1995 to 2023. A total of 61 publications were identified with PRISMA 2020. The qualitative findings showed that (1) most studies of transcreation focus on literary and advertising, while other fields of audiovisual, news and political, training and interpreting need to be explored; (2) research foci of transcreation strategies, culture and ideology gain more attention while transcreation process and evaluation, localization and persuasion have not been much examined; (3) content analysis is most frequently adopted while other qualitative methods are less used. Besides, there is a lack of using quantitative and mixed methods; (4) systematical functional linguistics is often used as a pointcut to examine strategies of transcreation. Besides, multimodal social semiotics is used to explore transcreation through texts, pictures and videos. Other linguistic theories and cross-disciplinary theories remain unexplored in transcreation. In conclusion, this study provides a review of transcreation and translation studies and reveals some research gaps that could enlighten future studies.